2019
DOI: 10.3390/ijms20236059
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Bones Deficient in Fibrillin-1 Microfibrils Reveals Pronounced Sex Differences

Abstract: Defects in the extracellular matrix protein fibrillin-1 that perturb transforming growth factor beta (TGFβ) bioavailability lead to Marfan syndrome (MFS). MFS is an autosomal-dominant disorder, which is associated with connective tissue and skeletal defects, among others. To date, it is unclear how biological sex impacts the structural and functional properties of bone in MFS. The aim of this study was to investigate the effects of sex on bone microarchitecture and mechanical properties in mice with deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Currently, there is only limited information available regarding sex-dependent expression rates of fibrillin-1 from which asprosin is derived after furin-mediated cleavage within the C-terminal region. However, analysis of fibrillin-1 mutant mice revealed sex-dependent differences in thoracic aorta contractility, as well as aortic media injury 36 , 37 . Interestingly, addition of 17β-estradiol was found to promote fibrillin-1 production by human aortic smooth muscle cells, but not by fibroblasts 38 , suggesting a sex- and tissue-dependent regulation of fibrillin-1 expression which may explain the observed increase of asprosin in serum samples from females.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there is only limited information available regarding sex-dependent expression rates of fibrillin-1 from which asprosin is derived after furin-mediated cleavage within the C-terminal region. However, analysis of fibrillin-1 mutant mice revealed sex-dependent differences in thoracic aorta contractility, as well as aortic media injury 36 , 37 . Interestingly, addition of 17β-estradiol was found to promote fibrillin-1 production by human aortic smooth muscle cells, but not by fibroblasts 38 , suggesting a sex- and tissue-dependent regulation of fibrillin-1 expression which may explain the observed increase of asprosin in serum samples from females.…”
Section: Discussionmentioning
confidence: 99%
“…In various diseases, including CVD, there are fundamental differences between the sexes in manifestation and outcome, as well as the response to treatment [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 ]. Overall, sex differences are generally attributed to genetic and epigenetic mechanisms, regulating major biological processes, including cell death, extracellular matrix deposition and inflammation, as well as sex hormones and their receptors [ 77 , 82 , 83 , 86 , 87 , 88 , 89 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 ,…”
Section: Effects Of Biological Sexmentioning
confidence: 99%
“…Interestingly, it has been shown that the simultaneous presence of a single copy of TIMP1 and TIMP3 risk alleles raises the risk of aortopathy [ 61 ] ( Figure 1 ). TIMP imbalance is also responsible for ECM degradation that leads to excessive TGF-β signaling and the activation of SMAD signaling, both of which have been linked to an increase in fibrosis and inflammation in the aortas of patients with TS, similar to other rare disorders [ 63 , 64 ]. This over-activation leads to the induction of metalloproteases and eventually to aortic dilation and dissection [ 60 ].…”
Section: Cardiovascular Manifestations In Sex Chromosome Disordersmentioning
confidence: 99%